Upaya meningkatkan kemampuan berbicara anak melalui kegiatan berwirausaha jual beli pada kelompok usia 5-6 tahun TK Muslimat NU Masyitoh 19 “Annisa” Jenggot Pekalongan tahun ajaran 2020-2021 - Nanik Utami (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The general objective of this study is to improve the speaking ability of children in the 5-6 years age group totaling 14 children consisting of 9 boys and 5 girls. Muslimat NU Masyitoh 19 “Annisa” Beard Pekalongan obtained by using the method of observation and documentation. The data obtained by observation were analyzed qualitatively by processing data from observations in activities and evaluating children's speaking skills through buying and selling entrepreneurship activities in the form of percentages. The results of this study showed that the results of observations in the 5-6 years age group were initially 14.29%. This was because there was no renewal of learning in children. After improving the action through buying and selling entrepreneurship activities in the classroom using tools and materials in the role center, the results in the first cycle were 57.14% while in the second cycle the buying and selling entrepreneurship activities were by selling agar directly to parents around 85.71 %, This shows an increase in children's speaking skills through buying and selling entrepreneurship activities carried out in cycles I and II in the 5-6 year age group of Muslimat NU Masyitoh 19